2008
DOI: 10.1523/jneurosci.0303-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of an Allosteric Kinetics of NMDA Receptors for Spike Timing-Dependent Plasticity

Abstract: Spike timing-dependent synaptic plasticity (STDP) plays an important role in neural development and information processing in the brain; however, the mechanism by which spike timing information is encoded into STDP remains unclear. Here, we show that a novel allosteric kinetics of NMDA receptors (NMDARs) is required for STDP. We developed a detailed biophysical model of STDP and found that the model required spike timing-dependent distinct suppression of NMDARs by Ca 2ϩ -calmodulin. This led us to predict an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(110 citation statements)
references
References 141 publications
(134 reference statements)
4
106
0
Order By: Relevance
“…If we apply the same STDP model not only to RGC-TN synapses but also to TN-TN synapses, all of the TN-TN synapses may be potentiated by the repetitive exposure of the retina to the fast-moving light bar. This corresponds to the situation in which burst firings in both pre-neurons and postneurons lead to potentiation, regardless of the order of the firings in pre-neurons and post-neurons (Froemke et al, 2006;Urakubo et al, 2008). In this case with STDP at TN-TN synapses, stronger early transient feedforward signals and the decrease in the transition threshold of feedback excitation due to the potentiation of all TN-TN synapses are similarly likely to lead to the development of direction selectivity.…”
Section: Stdp In Tn-tn Synapsesmentioning
confidence: 93%
See 3 more Smart Citations
“…If we apply the same STDP model not only to RGC-TN synapses but also to TN-TN synapses, all of the TN-TN synapses may be potentiated by the repetitive exposure of the retina to the fast-moving light bar. This corresponds to the situation in which burst firings in both pre-neurons and postneurons lead to potentiation, regardless of the order of the firings in pre-neurons and post-neurons (Froemke et al, 2006;Urakubo et al, 2008). In this case with STDP at TN-TN synapses, stronger early transient feedforward signals and the decrease in the transition threshold of feedback excitation due to the potentiation of all TN-TN synapses are similarly likely to lead to the development of direction selectivity.…”
Section: Stdp In Tn-tn Synapsesmentioning
confidence: 93%
“…Synaptic modification was induced through STDP in the synapses from the RGCs to the TNs. As a synaptic learning rule, we used a simple STDP model, which was made by simplifying the detailed molecular STDP model (Urakubo et al, 2008. A detailed description of the simple STDP model is provided in the supplemental material (available at www.jneurosci.org).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is very difficult to test this conjecture experimentally. It has also been suggested that one of several alternative mechanisms may serve as the second coincidence detector required for the induction of LTD by spike and triplet pairing stimulation protocols [42,45,66]. By elaborating the secondary messenger pathways in the plasticity model to more closely replicate the activity of CaM, CaMKII, PP1, PP2A, I1 and other proteins implicated in plasticity expression, as well as additional sources of internal and external Calcium influx, it may be possible to more accurately appraise the contributions made by bAPs to synaptic plasticity [7,46,67].…”
Section: Discussionmentioning
confidence: 99%